Flow in Shortened Round Supersonic Nozzle with a Bell-shaped Tip - Nataliya, Pryadko; Hennadii, Strelnikov; Katerina, Ternova (Current Approaches in Engineering Research and Technology Vol. 8, 2024)
The present study aimed to generalize the study results of supersonic flows in a shortened nozzle with a bell-shaped tip and analyze the effect of the base nozzle length, different connection tip angles with the conical nozzle part, inlet and external pressure on the flow characteristics in the nozzle. The flow in a shortened nozzle with a bell-shaped nozzle is considered. A comparison of the wave structures of supersonic gas flow was carried out in shortened nozzles with short and long tips formed by compression and stretching of the original bell-shaped tip for connection with the long and short conical base nozzle part, respectively, and with the same nozzle length. The influence of connection angles of the conical nozzle part with the bell-shaped tip was analyzed. The flow characteristics were observed under operation conditions at sea level, in the upper atmosphere layers and different pressure values at the nozzle inlet. The calculation results correlated satisfactorily with the flow experimental study results.